UJI KOMPARATIF HORMON HUMAN CHRORIONIC GONADOTROPHIN (HCG), OVAPRIM, DAN SPAWNPRIM PADA PEMIJAHAN IKAN LELE SANGKURIANG (Clarias sp.) - Nova Yulianti; Deny Sapto Chondro Utomo; Berta Putri (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
The results of spawning in sangkuriang catfish farming do not always go according to the expected results, as many eggs died before hatcing. Therefore, it is necessary to use spawning hormones which can improve egg quality in order to increase profits in cultivation. This research was aimed to determine the difference on success performance of sangkuriang catfish using HCG, Ovaprim, and Spawnprim. This research used a randomized block design (RAK) with 3 treatments i.e P1 (HCG 500 IU/kg), P2 (Ovaprim 0,5 ml/kg), P3 (Spawnprim 0,5 ml/kg) and 3 groups of repetition i.e K1 (spawning group day-1), K2 (spawning group day-2), and K3 (spawning group day-3). The results of this research showed that using Ovaprim hormone had the highest value than other treatments like on latent time 606±17,78 minutes, egg fertilization percentage 75±2,65%, and egg hatching percentage 69,33±5,69%. Then on egg fecundity and egg diameter showed no significant effect with other treatments.